Pengaruh Pemeriksaan Pajak Dan Penagihan Pajak Terhadap Kepatuhan Pajak Pertambahan Nilai (PPn) Pada KPP Pratama Jakarta Pasar Rebo Pada Tahun 2022 - Oktaviani, Anggie Yuni; Safitry, Martina (Jurnal Pajak Vokasi (JUPASI), 2024)
One of the Primary Revenue Streams for the State is Value-Added Tax (VAT). However, revenue deficits often stem from taxpayer non-compliance with Tax Regulations. This study aims to explore how tax audits and collection procedures affect VAT compliance at the Jakarta Pasar Rebo Tax Office in 2022. Employing a Quantitative Approach, this study employs the Slovin formula for sample selection. Data collection involves distributing questionnaires via Google Form, sourced from the Jakarta Pasar Rebo Tax Service Office. The findings of this study indicate that (1) Tax Audits and Collections significantly Influence VAT Compliance at the Jakarta Pasar Rebo Tax Office in 2022, (2) The results of the hypothesis t-test show a significant influence. From the t-test results yielding 2.176 > t-table 2.03. Tax examination yields an Unstandardized value of 0.388 points, (3) In the t-test, the result of the F-statistic is 48.823 > f-table = 3.28, meaning that all independent variables together have an effect on the dependent variable, (4) The determination test results reveal an R ² value of 0.742, suggesting a robust simultaneous relationship among all variables, contributing to 74.2% of compliance. The remaining 25.8% variation is attributable to unexamined factors